"This is who I am and this is what I'm carrying": examining self-disclosure in forensics. (1st October 2020) - Copeland, Kristopher; Woodall, Ant
Abstract: The forensic activity provides an opportunity for students to tackle a variety of topics and subjects. Many topics, specifically in individual events, can provide an outlet for competitors to self-disclose information to audience members. For this qualitative study, we interviewed 13 participants to understand how forensic competitors use self-disclosure within forensics. Our findings suggest that competitors use forensic competitions to implicitly and explicitly self-disclose private information. Additionally, competitors noted using negative experiences with disclosure and general forensic norms to develop privacy boundary rules when determining whether to self-disclose. Most importantly, the study results provide descriptions of and explanations for the types of communication strategies competitors incorporated when considering self-disclosures in forensics. We discuss implications for communication privacy management theory and for competitors, forensic practitioners, and communication scholars.